عہد ِنبوی میں سماجی عدل وانصاف: Social Justice in Prophet’s Regime - Dr.Yasin Mazhar Siddiqui (Seerat Studies, 2023)
The Holy Book of Allah encompasses all basic concepts and theories of social justice and welfare of society while the life and sayings of the Holy Prophet (SAW) explain it theoretically as well as practically. Islam provides a complete code of justice and system of welfare whereas other religions and social systems cannot be considered equal to it. This reality has also been acknowledged at international level. The last Prophet (SAW) of Allah exercised and implemented social justice and welfare of society for the betterment of an individual and masses. It was an exemplary system which is unique, matchless and also everlasting till the Day of Judgment. It is obligatory for Muslim-Ummah to follow it for eternal salvation and collective good. The researcher has critically and analytically thrown full light upon this topic for general understanding and collective prosperity.